Pioneering digital platform ecosystems: The role of aligned capabilities and motives in shaping key choices and performance outcomes - Wormald, Audra; Shah, Sonali K.; Braguinsky, Serguey; Agarwal, Rajshree (Strategic Management Journal, 2023)
Abstract R esearch Summary We inductively analyze rich qualitative and quantitative data on the global census of pioneering mobile money firms to examine how firm characteristics shape digital platform ecosystem configuration choices regarding (a) internal versus external integration and (b) the creation of network externalities through open versus closed end‐user access. In contrast to received wisdom, we find pioneering firms were equally likely to engage in external and internal integration; moreover, diversifying entrants were less likely to internally integrate than startups. We uncover the important role of motives, in addition to capabilities, for creating alignment between pioneering firms and their partners. Such alignment was key for addressing path‐dependent implementation challenges through experimentation and navigating nascent industry uncertainty for success. Managerial Summary Our study showcases how enterprising firms pioneered and diffused mobile money, a digital platform that improves access to financial services. The successful take‐off and growth of this industry, as revealed by our inductive analysis, was contingent on aligned capabilities and motives among platform co‐providers and critical partners. We illuminate why and how pioneer capabilities and motives influenced key platform choices regarding internal versus external integration, and open versus closed end‐user access. These choices then created different implementation challenges. The successful pioneers navigated these challenges to create a robust ecosystem for network effects by engaging in two actions: they developed lasting partner relationships, and they experimented to determine distinct demand segments, identify unmet needs, and develop value propositions.